The Council of Europe and the International Cooperation preventing and fighting against International Organized Crime - Campina, Ana (2022)
Understanding the world and Humanity changes due the Globalization phenomenon allows to identify the special conditions created that promote the implementation and the dissemination of the International Organized Criminality, in short time, affecting the International Community in all dimensions. As one of the most serious threats to the Rule of Law, violating the national legal systems and the International Law, being especially dangerous to the states and human lives in a global context. The International, regional and (most of) national juridical and judicial systems recognize the International Organized Criminality as a emergent problem that needs to be in the top of the political agenda and of the action by the Institutions aiming to prevent and fight their evolution, their dangerous damages and consequences to all their target – human and institutional. Although all difficult but effective legal, political, economic, and social work in this fight, mainly by the United Nations in cooperation with International Organizations and States, the Council of Europe (CoE) assumed their responsibility to protect their State Members, their citizens, and the rest of the world by inherence. There is an enormous political and legal work, with a straight position based on their main structure document, the European Convention on Human Rights, but with the specialized work teams, understanded as need in each case. Consequently, the CoE has a continuous production of legislation and management of procedures and activities, as well as International political and governance diplomatic relations in networks, in compliance with the International Law facing the challenge that context obliges permanently. Since 1959, with the Convention on Mutual Assistance in Criminal Matters, the strategic action promoted is the multidimensional International Cooperation between all “actors” in the International Community, preventing the violation of the International Law, generated conditions to apply the International Penal Law and developing policymaking articulated with the real contexts and needs. Within International Community, the Cooperation is the best key to join procedures to transcend the difficulties and constraints to achieve to the prevention and fight against the International Organized Criminality. This scientific research is being developed based on juridical, criminal, and political methodology, mainly qualitative, but presenting statistic data to demonstrate the results discussed.